Analisis Sosialisasi DBLM Dan Literasi Terhadap Minat Masyarakat Bertransasksi Di Bank Sumut Syariah ( Studi Kasus Masyarakat Kec.Rahuning) - Rika ilmiwana Nur Hafizha (AGHNIYA : Jurnal Ekonomi Islam, 2022)
This study aims to determine the effect of DBLM socialization on the interest of the Rahuning community to make transactions at Islamic North Sumatra banks. This research is a type of quantitative research using primary data. The population used is the people of Rahuning sub-district, with a total sample of 278 customers. The sample and sampling in this study used the Non-Probability Sampling technique using the accidental sampling method, with a total sample of 74 respondents. The results of the research show that there is significant influence and socialization of DBLM on the public's interest in conducting transactions at Bank Sumut Syariah in Kec. Rahuning can be seen from the tcount value of 3.051 1.666 ttable and a significant value of 0.003 0.05. There is influence and significant Literacy on public interest in conducting transactions at Bank Sumut Syariah in Kec. Rahuning can be seen from the tcount value of 2.163 1.666 ttable and a significant value of 0.034 0.05. The R Square value of 0.229 means that 22.9% of the public's interest in making transactions at Bank Sumut Syariah Kec. Rahuning explained that the influence of DBLM Socialization and Literacy variables and the remaining 77.1% could be explained by other factors not examined in this study.